Evaluation Results Interprofessional Bedside Rounds Activities Inpatient Room RSUD DR Rubini Mempawah - Linda Andreyani (Journal of Social Science, 2022)
Introduction Interprofessional Bedside Rounds are a case of collaboration carried out by the Interdisciplinary case. Professional Care Providers (PCA) consist of doctors, nurses, pharmacists, nutritionists, and physiotherapists in case management, which consists of complex cases, rare cases, rare cases found, and new trials involving patients and families that contribute to improving patients and improving the quality of services. It carried methods. The research on using a mixed methods approach with parallel quantitative and qualitative convergent designs it carried out together. It carried out qualitative analysis using a phenomenological study approach, while in quantitative research, a practiced descriptive. In-depth interviews with 5 PCA participants carried qualitative data collection out. Meanwhiles, quantitative research uses secondary data from observation documents on patient safety and PPA safety goals. The results of the qualitative analysis get nine topics: interprofessional collaboration, activity systematics, collaboration characteristics, experiences, perceptions, patient safety goals, PCA safety, autonomy, and competence. While the results of quantitative research got data on patient safety targets of 97.52% and PCA safety data of 98.49% by following national standards. The results of qualitative and quantitative studies complement and reinforce each other. The conclusions of this study suggest that interprofessional bedside rounds between PCA have a synergistic relationship for the establishment of communication and cooperation, as well as an increase in knowledge so that it can realize optimal goals of patient safety and PCA safety.